Model Bangkitan Perjalanan Penduduk Hunian Tetap (Studi Kasus Hunian Tetap Tondo) - Badwi, B.; Patunrangi, J.; Setiawan, A. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
The Tondo permanent residence is located in Tondo sub-district, Mantikulore sub-district, Palu city. This residence will have a traffic impact on the surrounding road network because the impact of development in the area where the residence is built will still be an increase in population, increase in income, increase in vehicle ownership and the construction of a number of public facilities which will generate traffic generation and attraction so that It is necessary to conduct research on socio-economic characteristics, movement characteristics and generation models. Data collection was carried out using primary data through a home interview survey. To produce a trip generation model in this study, multiple linear regression methods were used. The socio-economic characteristics of Tondo permanent residences are 37.66% of family members amounting to 3 people, 39.29% total income of Rp. 1,000,000 – Rp. 3,000,000, the number of 2-wheeled vehicle owners is 40.58% who owns 2 units, the number of 4-wheeled vehicle owners is 88.64% and does not own a car and the travel intensity is 41.23%, amounting to 5 trips, while the characteristics of population movement in Tondo permanent residences namely the address before the earthquake 45.13% came from West Palu District, the type of work 49.03% worked as self-employed, the purpose of the trip 62.66% was to work, the education level of 79.22% was high school and the destination of the trip was 24.03% Head to Mantikulore District. The trip generation model is Y = 2.8642 + 0.9452 X3